2005
DOI: 10.1007/bf02703706
|View full text |Cite
|
Sign up to set email alerts
|

Fingernails as biological indices of metal exposure

Abstract: Metal determination in human tissues is the most common application of biological monitoring for screening, diagnosis and assessment of metal exposures and their risks. Various biopsy-materials may be used. This paper deals with the quantitative determination of Cd, Pb, Cr, Mn, Fe, Ni, Cu, and Zn concentrations in nails of male subjects exposed to these metals along with their respective controls, while working in locomotive, carriage and road ways workshops, and lead battery factories. The levels of Cd, Pb, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 12 publications
0
37
3
Order By: Relevance
“…The mean value found for Pb in nails in the present study was lower compared with other studies found in the literature ( Table 2). The highest values were measured in India [4], followed by Kenya, where the high Pb nail concentration of 34.4 μg g −1 was attributed to environmental exposures arising from the use of leaded gasoline [23].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The mean value found for Pb in nails in the present study was lower compared with other studies found in the literature ( Table 2). The highest values were measured in India [4], followed by Kenya, where the high Pb nail concentration of 34.4 μg g −1 was attributed to environmental exposures arising from the use of leaded gasoline [23].…”
Section: Discussionmentioning
confidence: 92%
“…Due to these inherent beneficial characteristics, several epidemiological studies have estimated individual's body burden of trace elements by using nails as the biological matrix [3][4][5][6][7]. However, background values for toxic and essential elements in nails, especially children, are still scarce [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cr 2 O 7 2À becomes significant when total Cr(VI) concentrations are >52 mg/L, or even dominate when total Cr(VI) concentrations are >1.56 g/L Total amount in human body 0.4-6 mg Iyengar (1989); Pechova and Pavlata (2007) Serum 0.01-0.38 μg/L Anderson et al (1985); Brune et al (1993); Christensen et al (1993); Moukarzel (2009); Pechova and Pavlata (2007); Sunderman et al (1989); Torra et al (1999) Blood 0.12-0.67 μg/L Christensen et al (1993); Pechova and Pavlata (2007) Urine 0.05-1.8 μg/L Apostoli et al (1997); Brune et al (1993); Kiilunen et al (1987) Saliva 0.55-0.70 μg/L De Souza and De Menezes (2008) Breast milk 0.06-1.56 μg/L Casey and Hambidge (1984); Kumpulainen et al (1983) Lung 130-1375 μg/kg (wet weight) Raithel et al (1993); Raithel et al (1988); Raithel and Schaller (1990) Liver 5-15 μg/kg Moukarzel (2009) Spleen 7-29 μg/kg Moukarzel (2009) Nail 0.52-172.92 mg/kg Mehra and Juneja (2005); Takagi et al (1988) Hair 234-3,800 μg/kg Afridi et al (2006); Hunt et al (1985); Iyengar (1989); Nowak and Kozlowski (1998); Sukumar and Subramanian (2003); Takagi et al (1986) Teeth 7200-35,000 μg/kg Nowak and Kozlowski (1998) Skeletal tissues 5-15 μg/kg Iyengar (1989) Muscle 5-10 μg/kg Iyengar (1989) Skin 50-200 μg/kg Iyengar (1989) (Palmer and Wittbrodt 1991;Palmer and Puls 1994); however, such high Cr(VI) concentrations are not...…”
Section: Introductionmentioning
confidence: 97%
“…Zinc participates in the synthesis of insulin and improves its transport to the cells acting at the receptor and post-receptor levels. Blood, hair, and nails analyses have shown a direct association between zinc deficiency and diabetes [14,36,37]. Under specific conditions zinc can be an active participant in apoptosis of pancreatic islets cells [38].…”
Section: Discussionmentioning
confidence: 99%